Influence of carbohydrate mouth rinsing on running and jumping performance during early morning soccer scrimmaging - Pribyslavska, V.; Scudamore, E. M.; Johnson, S. L.; Green, J. M.; Stevenson Wilcoxson, M. C.; Lowe, J. B.; O'Neal, E. K. (European Journal of Sport Science, 2016)
Carbohydrate mouth rinse (CMR) is a novel method proposed to enhance endurance performance lasting = 60 min. The current study examined the influence of CMR on anaerobic performance tasks in 11 collegiate female soccer players after an overnight fast. Athletes completed two experimental sessions, during which carbohydrate (CHO; 6% maltodextrin) or taste- and colour-matched placebo (PLA) mouth-rinse solutions were administered in a counterbalanced, double-blinded design. Three rounds of a 5-min scrimmage bout and series of performance tests including a single countermovement vertical jump (1VJ), a set of four consecutive vertical jumps, a 72-m shuttle run (SR72) and 18-m sprint comprised each trial. Thirst sensation (TS), session TS, ratings of perceived exertion (RPE) and session RPE were assessed as secondary outcomes. The first SR72 approached significance (p = 0.069), but no significant between-trials differences were observed for any of the mean performance tasks. The highest 1VJ scores did not differ for the first (CHO = 47.3 ± 3.4, PLA = 47.7 ± 3.5 cm; p = 0.43), second (CHO = 48.0 ± 4.1, PLA = 47.9 ± 3.5 cm; p = 0.82) or third bout (CHO = 47.4 ± 3.9, PLA = 48.1 ± 3.9 cm; p = 0.26). TS approached significance (p = 0.053) during the first bout. No significant differences (p > 0.05) were found for any of the perceptual variables. Current results fail to support ergogenic influence of CMR on anaerobic performance tasks in collegiate female athletes.